Indoleamine 2, 3-Dioxygenase-Dependent Neurotoxic Kynurenine Metabolism Contributes to Poststroke Depression Induced in Mice by Ischemic Stroke along with Spatial Restraint Stress. (30th December 2018) - Koo, Young Soo; Kim, Hyunha; Park, Jung Hwa; Kim, Min Jae; Shin, Yong-Il; Choi, Byung Tae; Lee, Seo-Yeon; Shin, Hwa Kyoung
Abstract : Aim . Poststroke depression (PSD), which occurs in approximately one-third of stroke survivors, is clinically important because of its association with slow functional recovery and increased mortality. In addition, the underlying pathophysiological mechanisms are still poorly understood. Methods . We used a mouse model of PSD to examine the neurobiological mechanisms of PSD and the beneficial effects of aripiprazole, an atypical antipsychotic drug. PSD was induced in mice by combining middle cerebral artery occlusion (MCAO) with spatial restraint stress. The body weight, sucrose preference, and forced swim tests were performed at 5, 7, and 9 weeks and the Morris water maze test at 10 weeks after completing MCAO and spatial restraint stress. Results . Mice subjected to MCAO and spatial restraint stress showed significant depressive-like behavior in the sucrose preference test and forced swim test as well as cognitive impairment in the Morris water maze test. The PSD-like phenotype was accompanied by an indoleamine 2, 3-dioxygenase 1 (IDO1) expression increase in the nucleus accumbens, hippocampus, and hypothalamus, but not in the striatum. Furthermore, the increased IDO1 levels were localized in Iba-1(+) cells but not in NeuN(+) or GFAP(+) cells, indicating that microglia-induced IDO1 expression was prominent in the PSD mouse brain. Moreover, 3-hydroxyanthranilate 3, 4-dioxygenase (HAAO), quinolinic acid (QUIN), and reactive oxygen species (ROS) were significantly increased in the nucleus accumbens, hippocampus, and hypothalamus of PSD mice. Importantly, a 2-week aripiprazole (1 mg/kg, per os ) regimen, which was initiated 1 day after MCAO, ameliorated depressive-like behavior and impairment of cognitive functions in PSD mice that was accompanied by downregulation of IDO1, HAAO, QUIN, and ROS. Conclusions . Our results suggest that the IDO1-dependent neurotoxic kynurenine metabolism induced by microglia functions in PSD pathogenesis. The beneficial effect of aripiprazole on depressive-like behavior and cognitive impairment may be mediated by inhibition of IDO1, HAAO, QUIN, and ROS.